2021
DOI: 10.1080/1828051x.2021.1901615
|View full text |Cite
|
Sign up to set email alerts
|

Effects of guanidinoacetic acid supplementation on zootechnical performance and some biometric indices in broilers challenged with T3-Hormone

Abstract: The objective was to elucidate the effects of dietary guanidinoacetic acid (GAA) supplementation on broiler performance, serum enzymes, oxidative biomarkers, mitochondrial activities, carcase traits, gross lesion of cardiac muscle and liver histopathology in broilers challenged with T 3 -hormone. A total-of-192 one-day-old mixed sexed broilers were randomly assigned in a two factorial design, including two dietary treatments; control diet supplemented with or without T 3 -hormone (1.5 ppm) and GAA diet (0.06%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 38 publications
(55 reference statements)
1
7
0
Order By: Relevance
“…Boney et al [ 17 ] recorded a 2.69% reduction in FCR from day 1 to 21 of age and a 2.55% reduction in FCR from day 36 to 42 of age in the diets supplemented with 0.06% GAA, regardless of the effect of the basal diet (conventional protein source or non-protein source), while BW was improved at 21 days of age compared to the non-supplemented groups. Khalil et al [ 13 ] reported that GAA at the level of 0.06% as the main effect on FCR resulted in a 4.03% reduction, regardless of the effect of dietary T3—hormone compared to the groups without GAA supplementation. Our results can be explained by the fact that GAA could improve the efficiency of energy utilization by replenishing ATP through the Cre-PCre shuttle system in addition to its Arg-sparing effect, which plays a central role in endogenous nitric oxide synthesis and maximizing growth performance of broiler chickens [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Boney et al [ 17 ] recorded a 2.69% reduction in FCR from day 1 to 21 of age and a 2.55% reduction in FCR from day 36 to 42 of age in the diets supplemented with 0.06% GAA, regardless of the effect of the basal diet (conventional protein source or non-protein source), while BW was improved at 21 days of age compared to the non-supplemented groups. Khalil et al [ 13 ] reported that GAA at the level of 0.06% as the main effect on FCR resulted in a 4.03% reduction, regardless of the effect of dietary T3—hormone compared to the groups without GAA supplementation. Our results can be explained by the fact that GAA could improve the efficiency of energy utilization by replenishing ATP through the Cre-PCre shuttle system in addition to its Arg-sparing effect, which plays a central role in endogenous nitric oxide synthesis and maximizing growth performance of broiler chickens [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The same authors reported in second experiment that 0.06% GAA supplementation to poultry by-product meal basal diets with different energy levels had no significant effects on carcass composition compared to the non-supplemented groups up to 41 days of age. Khalil et al [ 13 ] reported that carcass and cutting yield was not affected by 0.06% GAA supplementation compared to the non-supplemented group. However, another study showed a significant increase in both breast weight and yield in groups supplemented with 0.06% GAA as the main effect in basal diets with or without animal protein source compared to groups without GAA supplementation, while other carcass traits and relative organ weights were unaffected [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations